The Influence of Corporate Social Responsibility to Corporate Financial Performance - Jeanet Christanty Evans (Journal of Applied Accounting and Taxation, 2017)
This paper examines the relationship between corporate social responsibility and financial performance in Indonesian non-financial companies through stakeholder’s pressures. The researcher has chosen the Indonesia context as one of the world’s developing countries and it has undergone many changes over a short period of time in terms of economic, environmental and social changes. Purposive sampling was used to collect data relating to CSR and financial performance, tested by used regression model and generate mixed result. This paper contributes to the accounting literature by providing evidence from Indonesia that perceived the level of CSR in annual reports can have an influence on level of financial performance by stakeholder’s pressure.